Calcium Phosphate Based Three-Dimensional Cold Plotted Bone Scaffolds for Critical Size Bone Defects. (26th February 2014) - Bergmann, Christian J. D.; Odekerken, Jim C. E.; Welting, Tim J. M.; Jungwirth, Franz; Devine, Declan; Bouré, Ludovic; Zeiter, Stephan; van Rhijn, Lodewijk W.; Telle, Rainer; Fischer, Horst; Emans, Pieter J.
Abstract : Bone substitutes, like calcium phosphate, are implemented more frequently in orthopaedic surgery to reconstruct critical size defects, since autograft often results in donor site morbidity and allograft can transmit diseases. A novel bone cement, based on β -tricalcium phosphate, polyethylene glycol, and trisodium citrate, was developed to allow the rapid manufacturing of scaffolds, by extrusion freeform fabrication, at room temperature. The cement composition exhibits good resorption properties and serves as a basis for customised (e.g., drug or growth factor loaded) scaffolds for critical size bone defects. In vitro toxicity tests confirmed proliferation and differentiation of ATDC5 cells in scaffold-conditioned culture medium. Implantation of scaffolds in the iliac wing of sheep showed bone remodelling throughout the defects, outperforming the empty defects on both mineral volume and density present in the defect after 12 weeks. Both scaffolds outperformed the autograft filled defects on mineral density, while the mineral volume present in the scaffold treated defects was at least equal to the mineral volume present in the autograft treated defects. We conclude that the formulated bone cement composition is suitable for scaffold production at room temperature and that the established scaffold material can serve as a basis for future bone substitutes to enhance de novo bone formation in critical size defects.